Caracterização petrográfica, mineralógica e litoquímica das rochas vulcânicas do Gráben Jaibaras-CE - NASCIMENTO, Rosemery da Silva (Universidade Federal do Pará, 2023)
The studied area is located in the northwest region of Ceará, in the domain of the Borborema Province and comprises two sectors along the Gráben Jaibaras. The study focused on the Parapuí Suite, which comprises a succession of volcanic rocks related to the Neoproterozoic. Three main groups of rocks were identified in the suite, including alkaline basalts (andesine-basalts, ilmenite-basalts and trachybasalts), rhyolites and volcanoclastic rocks that occur interspersed with the arcosian sandstones of the Jaibaras Group. The alkaline basalts, the most abundant types in the suite, occur in successions of extensive flows of massive and amygdaloid lavas, comprising holocrystalline or hypovitreous variations with porphyritic, serial or aphyric textures. Features indicative of very rapid cooling with acicular, dovetail, skeletal and resorption crystals, embedded in glass, demarcate interfaces between the various levels of effusions. The main minerals comprise labradorite with variations for andesine, titanoaugite and subordinately alkali-feldspar, olivine, ilmenite, pyrite, titanite and apatite. The minerals present in the tonsils are carbonates, zeolites, quartz, epidote, chlorite and prehnite. Chemically, basalts are characterized by high levels of alkalis, TiO2 and P2O5, and rare earth elements with an inclined pattern, showing enrichment in light REE, small negative anomaly of europium and moderate and high (La/Lu)N ratio. In the classification diagrams they are located in the field of alkaline basalts and/or in the interphase between tholeiitic and alkaline basalts. In the spiderograms of trace elements and rare earths, the various analyzed samples present a similar geochemical signature, despite the transformations in low metamorphic degree existing in these rocks, which reveals a compositional homogeneity of this magmatism. Interpretations of tectonic paleoenvironment suggest that it corresponds to continental intraplate magmatism. The rhyolites represent little expressive and rare flows in the suite, constituting porphyritic rocks in which bipyramidal quartz phenocrysts stand out, corroded, immersed in a felsitic, spherulitic microcrystalline matrix and with fluid structures. Chemically, they are rich in SiO2 and alkalis, with low Na2O/K2O ratios. The behavior of minor and trace elements in the spiderograms highlights that the geochemical signatures of these rocks contrast with the basalts. The Parapuí Suite was established through intense volcanism during the extensional tectonic installation of the Jaibaras Basin in the rift stage. It represents an intracontinental alkaline magnetism with a bimodal contribution fundamentally of a basaltic and alkaline rhyolitic nature, in a subaerial environment with effusions and explosions.